2017
DOI: 10.3892/etm.2017.5021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑21 regulates the viability and apoptosis of diffuse large B‑cell lymphoma cells by upregulating B cell lymphoma‑2

Abstract: Abstract. Diffuse large B-cell lymphoma (DLBCL), one of the most frequently diagnosed non-Hodgkin lymphoma (NHL), is partly attributed to hereditary factors. is an oncogenic substance that induces NHL and primarily targets tumor-suppressive molecules, such as B cell lymphoma-2 (Bcl-2). The present study explored whether Bcl-2, targeted by miR-21, would affect the development of NHL. Specimens were harvested from 55 patients with DLBCL who had undergone surgical treatment. Expression levels of miR-21 and Bcl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Twenty-one studies analyzed the expression of miRNAs by comparing DLBCL cases vs healthy controls [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. These 21 studies provided a total of 140 differentially expressed microRNAs in DLBCL patients compared with healthy control individuals as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies analyzed the expression of miRNAs by comparing DLBCL cases vs healthy controls [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. These 21 studies provided a total of 140 differentially expressed microRNAs in DLBCL patients compared with healthy control individuals as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the miRNAs that were concordantly deregulated in more than two studies, we identified two miRNAs that were repeatedly reported to be up-regulated in DLBCL patients (miR-155-5p [17,22,24,26,28,30,32,33,34], miR-21-5p [19,22,26,28,33,36], although some studies did not find a significant association (miR-155-5p [27,29], miR-21-5p [27,32]).We also identified two miRNAs with contradictory results. On the one hand, miR-150-5p was found to be down-regulated in DLBCL patients in four studies [18,28,31,32] and contradictorily up-regulated in DLBCL patients in another study [29], while no significant association was reported in the remaining study [27].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated miRNA profiles in diffuse large B-cell lymphoma (DLBCL) [41][42][43][44][45][46]. miR-181a-5p is reported to be upregulated in peripheral blood of acute lymphoblastic leukemia compared with normal peripheral blood mononuclear cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…According to the canonical miRNA-mRNA interaction, upregulation of these posttranscriptional elements in VRL may promote downregulation of important genes responsible for B-cell lymphoma. In fact, 21-5p has been associated with survival and proliferation of malignant cells in DLBCL [43,72].…”
Section: Discussionmentioning
confidence: 99%
“…In diffuse large B-cell lymphoma (DLBCL), the most common invasive NHL, more than 100 miRNAs have been reported to be deregulated (40,41,89,90), including numerous miRNAs with identified biological functions, such as miR-15a/16, miR-21, miR-34a, miR-106, miR-146a/b, miR-150, and miR-155 (91)(92)(93)(94)(95)(96)(97)(98). A study reported 2,632 novel lncRNAs specifically expressed in DLBCL clinical samples compared with normal B cells, nearly half of which were differentially expressed and clustered across different groups of DLBCL samples (99), suggesting that these lncRNAs may participate in DLBCL pathogenesis.…”
Section: Ncrna Dysregulations In B-cell Lymphomamentioning
confidence: 99%